Partnership A history of Goldman Sachs - Charles D Ellis; ELLIS (Charles D) (London Penguin books Ltd, 2008)
The Partnership chronicles the most important periods in Goldman Sachs?s history and the individuals who built one of the world?s largest investment banks. Charles D. Ellis, who worked as a strategy consultant to Goldman Sachs for more than thirty years, reveals the secrets behind the firm?s continued success through many life-threatening changes. Disgraced and nearly destroyed in 1929, Goldman Sachs limped along as a break-even operation through the Depression and WWII. But with only one special service and one improbable banker, it began the stage-by-stage rise that took the firm to global leadership, even in the face of the world-wide credit crisis.
Keywords: Partnership